THE EFFECT OF FIT BETWEEN NATURAL ENVIRONMENTAL APPROACH AND BUSINESS STRATEGY ON PERFORMANCE - Budi Suprapto (KINERJA, 2006)
This field study of 83 chemical firms examines the effect of fit between natural environmental approaches and business strategies on performance. Using factor analysis, the study found three approaches to their natural environment: prevention, information, and correction. Moreover using cluster analysis, the sample firms can be grouped into three categories based on business strategy typology: prospector, defender, and reactors. The findings from regression analysis suggested that prevention, information, and correction approaches insignificantly affect on performance. Compare to reactors, defenders and prospectors realized significant improvements on performance. The prevention has stronger and significant effect on ROA among prospectors than among defenders. The information has stronger and significant effect on sales growth among prospectors than among defenders. However, the significant effects were not found in the interaction between correction and prospectors. Neither was it found between correction and defenders on performance. In general, the results of those findings support the argument that firms benefit from the adoption of environmental policy when natural environmental approaches fit the business strategy.Keywords: Natural Environmental Approach, Business Strategy and Performance